A copper-based denitration catalyst based on a multi-level pore ssz-39 carrier and a preparation method thereof
Patent Information
- Application Number
- CN202410570770.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-09
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2044-05-09
AI Technical Summary
[0004]虽然Cu-SSZ-39分子筛拥有诸多优势用于NH3-SCR催化反应,但是SSZ-39的微孔尺寸极大地限制了反应物和生成物的扩散和传质,而且影响了金属活性位点
[0031] 1. In the preparation process of SSZ-39, this invention adds salts such as sodium carbonate. The use of salts can induce the aggregation of nanocrystals and shorten the hydrothermal crystallization time by accelerating nucleation and crystal growth. During the subsequent calcination process, the salts release a large amount of CO2 and H2O to promote the formation of hierarchical porous structures. The construction of hierarchical porous structures can improve the diffusion and mass transfer of reactants and products, improve the dispersibility of metal species, increase the active sites of the reaction, and improve the anti-coking performance of the catalyst.
Smart Images

Figure CN118663315B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a copper-based denitration catalyst based on a hierarchical porous SSZ-39 support and its preparation method, belonging to the field of molecular sieve catalyst technology. Background Technology
[0002] Nitrogen oxides (NO) x NOx is one of the most serious air pollutants, causing a range of environmental problems such as acid rain, the greenhouse effect, and photochemical smog. Currently, eliminating NOx... x The most effective and widely used technology is ammonia selective catalytic reduction (NH3-SCR). The key to this technology lies in developing denitrification catalysts that are highly active, selective, and water-resistant.
[0003] Among numerous catalysts, Cu-based molecular sieves are considered ideal catalysts for the NH3-SCR reaction due to their excellent redox capabilities, suitable acidity, and high hydrothermal stability. SSZ-39 molecular sieves have an AEI structure with mirror-image arrangement of adjacent six-membered rings, and the eight-membered ring channels within them have small pore sizes. This gives SSZ-39 greater advantages in catalytic activity and hydrothermal stability, making it a widely studied support for novel Cu-based catalysts.
[0004] Although Cu-SSZ-39 molecular sieves possess numerous advantages for NH3-SCR catalytic reactions, the micropore size of SSZ-39 significantly restricts the diffusion and mass transfer of reactants and products, and also affects the metal active sites. Furthermore, the agglomeration of metal particles during calcination increases diffusion resistance within the gas molecular sieve, inhibiting denitrification performance. Therefore, it is necessary to propose a simple and easy-to-operate method for preparing Cu-SSZ-39 molecular sieves with high catalytic activity. Summary of the Invention
[0005] The technical problem to be solved by this invention is to provide a copper-based denitration catalyst based on a hierarchical porous SSZ-39 support, which exhibits excellent low-temperature denitration activity and a wide temperature activity range, with a minimum ignition temperature T. 80 Below 110℃, the NO conversion rate reaches over 90% within a temperature range of 120℃ to 500℃, and the NO conversion rate can reach 100% within a temperature range of 180℃ to 350℃. The catalyst of this invention also has good water resistance; under water content test conditions, the NO conversion rate can still maintain over 90% within a temperature range of 120℃ to 500℃.
[0006] Meanwhile, this invention provides a method for preparing a copper-based denitration catalyst based on a hierarchical porous SSZ-39 support. The method involves first aging a silicon source, zeolite seed crystals, an organic structure directing agent, deionized water, salt substances, and a copper source into a gel, followed by crystallization, washing, centrifugation, drying, and calcination to obtain a hierarchical porous Cu-SSZ-39 molecular sieve. Subsequently, the hierarchical porous molecular sieve is added to a metal complex composed of a copper source and an inducing agent for exchange. After washing, centrifugation, drying, and calcination again, a copper-based denitration catalyst based on a hierarchical porous SSZ-39 support is obtained.
[0007] Meanwhile, this invention provides an application of a copper-based denitration catalyst based on a hierarchical porous SSZ-39 support in the selective catalytic reduction reaction of ammonia (NH3-SCR), and more particularly, an application of a copper-based denitration catalyst based on a hierarchical porous SSZ-39 support in the aqueous selective catalytic reduction reaction of ammonia (NH3-SCR).
[0008] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing a copper-based denitration catalyst based on a hierarchical porous SSZ-39 support includes the following steps:
[0010] Step 1: The silicon source, zeolite seed crystals, organic structure directing agent, deionized water, salt substances, and copper source are thoroughly mixed and then aged to obtain gel A. Gel A is synthesized by microwave hydrothermal synthesis. The obtained synthetic gel A is heated and stirred at 100-200℃ for 0.5-12h to crystallize. After cooling to room temperature, the obtained product is washed with deionized water and centrifuged for recovery. Then it is dried at 40-120℃ for 4-16h. After drying, the solid product is calcined at 400-650℃ for 3-12h and cooled to obtain hierarchical porous Cu-SSZ-39 molecular sieve.
[0011] Step 2: Dissolve the copper source in deionized water to form a homogeneous solution. Add an inducing agent while stirring continuously to form a stable metal complex B. Then add a hierarchical porous Cu-SSZ-39 molecular sieve and stir at 10–100 °C for 4–12 h. After stirring, wash and centrifuge to obtain a solid product. Then dry at 40–120 °C for 4–16 h. After drying, calcine the solid product at 400–650 °C for 3–12 h and cool to obtain a copper-based denitration catalyst based on a hierarchical porous SSZ-39 support.
[0012] Preferably, in step 1, the mass ratio of zeolite seed crystals, silicon source, organic structure directing agent, deionized water, salt substances, and copper source is 1:(8.69–11.19):(7.22–7.49):(9.47–11.97):
[0013] (0.13~0.22): (0.05~0.30).
[0014] Preferably, in step 2, the mass ratio of hierarchical Cu-SSZ-39 molecular sieve, copper source, deionized water, and inducing agent is 1:(2.8~3.725):(30~50):(0.52~1.345).
[0015] Preferably, in step 1,
[0016] The salts are selected from one of sodium carbonate, potassium carbonate, iron carbonate, magnesium carbonate, and ammonium carbonate.
[0017] The silicon source is selected from one or two of amorphous silica, nano silica, tetraethyl orthosilicate, silica sol, or sodium silicate;
[0018] The zeolite seed crystals are selected from one of Y zeolite, Beta zeolite, ZSM-5 zeolite, or MOR zeolite;
[0019] The organic structure directing agent is selected from one of N,N-diethyl-2,6-dimethylpiperidine hydroxide, N,N-dimethyl-3,5-dimethylpiperidine hydroxide, and N-methyl-N-ethyl-2,6-dimethylpiperidine hydroxide;
[0020] The copper source is selected from one of copper nitrate, copper sulfate, and copper acetate.
[0021] Preferably, in step 2,
[0022] The copper source is selected from one of copper nitrate, copper sulfate, and copper acetate.
[0023] The inducing agent is selected from one of ammonia, ethylenediamine, triethylenetetramine, and tetraethylenepentamine.
[0024] Preferably, in step 1, the aging temperature of gel A is 20–100°C, and the aging time is 2–8 hours.
[0025] Preferably, in step 1, the microwave hydrothermal synthesis power is 300-600W, the heating temperature is 100-200℃, and the heating time is 4-48h.
[0026] Preferably, the continuous stirring and the stirring rate in this invention are both 450-550 rpm, and the vigorous stirring rate is 800-1000 rpm.
[0027] The preparation method of the present invention yields a copper-based denitration catalyst based on a hierarchical porous SSZ-39 support, in which hierarchical porous SSZ-39 serves as the support and Cu and induced CuO species are uniformly loaded as active sites.
[0028] The specific surface area of the catalyst is 673–690 m². 2 / g.
[0029] The present invention relates to the application of the copper-based denitration catalyst based on the hierarchical porous SSZ-39 support in the selective catalytic reduction reaction NH3-SCR of ammonia.
[0030] Compared with the prior art, the beneficial effects of the present invention are:
[0031] 1. In the preparation process of SSZ-39, this invention adds salts such as sodium carbonate. The use of salts can induce the aggregation of nanocrystals and shorten the hydrothermal crystallization time by accelerating nucleation and crystal growth. During the subsequent calcination process, the salts release a large amount of CO2 and H2O to promote the formation of hierarchical porous structures. The construction of hierarchical porous structures can improve the diffusion and mass transfer of reactants and products, improve the dispersibility of metal species, increase the active sites of the reaction, and improve the anti-coking performance of the catalyst.
[0032] 2. The Cu ion active sites of the present invention are synthesized in situ during the construction of hierarchical SSZ-39, avoiding the cumbersome Cu ion exchange steps. Furthermore, during the formation of hierarchical pores, the interaction between Cu ions and Al atoms in the molecular sieve framework facilitates the placement of Cu ions and adjusts their geometry and electronic structure, thereby further improving their catalytic performance and product selectivity.
[0033] 3. This invention uses ammonia and other inducing agents to form stable metal complexes with Cu ions. These complexes can be adsorbed and uniformly dispersed on the molecular sieve, forming stable and dispersed CuO during subsequent calcination. The use of these complexes effectively inhibits the migration and agglomeration of CuO particles, reducing the increase in molecular diffusion resistance caused by agglomeration, which is beneficial for the diffusion of substances during denitrification and improves the adsorption capacity of the catalyst. Simultaneously, highly dispersed CuO is obtained.
[0034] 4. The construction of a hierarchical porous structure can expose more... Acidic sites, Acidic sites can accelerate the adsorption of NH3 at higher temperatures, while Cu ion active sites are responsible for the adsorption of NH3 at lower temperatures. Therefore, using hierarchical porous SSZ-39 as a denitrification reaction carrier material is beneficial to improving the activity of NH3-SCR and broadening the reaction temperature window.
[0035] 5. In this invention, both Cu ions and CuO species coexist, and their synergistic effect promotes the [Cu(OH)] formation. + The generation of the -SSZ-39 species enhances the low-temperature denitrification activity of the catalyst. Furthermore, the charge interaction between the two promotes the oxidative transformation of Cu, which helps eliminate the adsorption competition of H2O for nitrate compounds, improving the catalyst's water resistance. Simultaneously, the presence of CuO and Cu ions facilitates the formation of an oxide layer on the catalyst surface, preventing water molecules from entering the catalyst interior and further enhancing its water resistance.
[0036] The catalyst of this invention comprises a support and catalytic components. The support is a hierarchical porous SSZ-39 molecular sieve, and the active components are copper and copper oxide. The catalyst is prepared by first aging a silicon source, zeolite seed crystals, an organic structure directing agent, deionized water, salt substances, and a copper source to obtain a gel. This gel is then crystallized, washed, dried, and further calcined to obtain a hierarchical porous Cu-SSZ-39 molecular sieve. Subsequently, an inducing agent is introduced into a copper ion solution to form a metal complex that exchanges with the hierarchical porous Cu-SSZ-39. After drying and calcination, a copper-based denitrification catalyst based on the hierarchical porous SSZ-39 support is obtained. The catalyst prepared by this invention exhibits excellent low-temperature denitrification activity and a wide temperature activity range, with a minimum ignition temperature T0. 80 Below 110°C, the NO conversion rate reaches over 90% within a temperature range of 120°C to 500°C, and can reach 100% within a temperature range of 180°C to 350°C. The catalyst of the present invention also exhibits good water resistance; under water content test conditions, the NO conversion rate can still remain above 90% within a temperature range of 120°C to 500°C. Attached Figure Description
[0037] Figure 1 These are the XRD patterns of Embodiment 1 and Comparative Example 4 of the present invention;
[0038] Figure 2 This is the XPS image of Cu element in the catalyst of Example 1 of the present invention;
[0039] Figure 3 The nitrogen adsorption-desorption isotherms of Example 1 and Comparative Example 4 of this invention are shown below.
[0040] Figure 4 The diagram shows a comparison of the denitrification performance of Examples 1, 2, 3, 1, 2, 3, 4, 5, and 6 of the present invention. Detailed Implementation
[0041] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments. The following embodiments are for illustrative purposes only and are not intended to limit the scope of the invention.
[0042] Example 1
[0043] A method for preparing a copper-based denitration catalyst based on a hierarchical porous SSZ-39 support includes the following steps:
[0044] Step 1: 2.2g of Y zeolite was dispersed in 20.83g of deionized water. Then, under continuous stirring, 21.52g of sodium silicate, 15.89g of N,N-dimethyl-3,5-dimethylpiperidine hydroxide, 3.1g of silica sol, 0.48g of sodium carbonate, and 0.22g of copper nitrate were added sequentially to the above solution. The mixture was aged at 40℃ for 5h to obtain gel A. The obtained gel A was crystallized by stirring at 140℃ for 1h using a 450W microwave hydrothermal synthesis method. After cooling to room temperature, the obtained product was washed with deionized water and centrifuged for recovery. Subsequently, it was dried at 60℃ for 12h. After drying, the solid product was calcined at 550℃ for 8h and cooled to obtain hierarchical porous Cu-SSZ-39 molecular sieve.
[0045] Step 2: Dissolve 5.6g of copper nitrate in 80g of deionized water to form a homogeneous solution. Add 1.04g of ammonia water under continuous vigorous stirring to form a stable metal complex B. Then add 2g of the above-mentioned hierarchical porous molecular sieve and stir at 30℃ for 6h. After stirring, centrifuge to obtain a solid product. Then dry at 60℃ for 12h. After drying, calcine the solid product in air at 550℃ for 8h and cool to obtain a copper-based denitration catalyst based on the hierarchical porous SSZ-39 support.
[0046] In this embodiment, preferably, the continuous stirring and stirring speeds are both 450 rpm, and the vigorous stirring speed is 800 rpm.
[0047] Figure 1 The XRD pattern shows the successful preparation of the SSZ-39 support and the loading of CuO species in Example 1.
[0048] Figure 2 The XPS spectrum of Cu element showed that there were two different valence states of Cu in Example 1, corresponding to Cu ions and copper oxide species, respectively.
[0049] Figure 3 The nitrogen adsorption-desorption isotherm diagram shows that Example 1 has the characteristics of hierarchical pores.
[0050] The copper-based denitration catalyst obtained in this embodiment uses hierarchical SSZ-39 as the support and uniformly loads Cu and inducible CuO species as active sites.
[0051] The copper-based denitration catalyst based on the hierarchical porous SSZ-39 support obtained in this embodiment was used for NH3-SCR. The catalyst was tableted and sieved to 20-40 mesh. The SCR activity test was conducted using the following gas components: 500 ppm NH3, 500 ppm NO, and a balance of 5 vol% O2 and N2. The SCR activity of the catalyst was tested at a temperature range of 80-500°C, 1 standard atmosphere, and a gas hourly space velocity of 60,000 h⁻¹.-1 It is carried out under the following conditions.
[0052] Example 2
[0053] A method for preparing a copper-based denitration catalyst based on a hierarchical porous SSZ-39 support includes the following steps:
[0054] Step 1: 3.1g of Beta zeolite was dispersed in 30.45g of deionized water. Then, under continuous stirring, 24.85g of sodium silicate, 22.52g of N,N-diethyl-2,6-dimethylpiperidine hydroxide, 2.1g of silica sol, 0.65g of potassium carbonate, and 0.31g of copper sulfate were added sequentially to the above solution, and the mixture was aged at 40℃ for 5h to obtain gel A. The obtained gel A was crystallized by stirring at 140℃ for 1h using a 450W microwave hydrothermal synthesis method. After cooling to room temperature, the obtained product was washed with deionized water and centrifuged for recovery. Subsequently, it was dried at 60℃ for 12h. After drying, the solid product was calcined in air at 550℃ for 8h and cooled to obtain hierarchical porous Cu-SSZ-39 molecular sieve.
[0055] Step 2: Dissolve 7.45g of copper sulfate in 80g of deionized water to form a homogeneous solution. Add 1.79g of ethylenediamine under continuous vigorous stirring to form a stable metal complex B. Then add 2g of the above-mentioned hierarchical porous molecular sieve and stir at 30℃ for 6h. After stirring, centrifuge to obtain a solid product. Then dry at 60℃ for 12h. After drying, calcine the solid product in air at 550℃ for 8h and cool to obtain a copper-based denitration catalyst based on the hierarchical porous SSZ-39 support.
[0056] In this embodiment, preferably, the continuous stirring and stirring speeds are both 450 rpm, and the vigorous stirring speed is 800 rpm.
[0057] The copper-based denitration catalyst based on the hierarchical porous SSZ-39 support obtained in this embodiment uses hierarchical porous SSZ-39 as the support and uniformly loads Cu and inducible CuO species as active sites.
[0058] The copper-based denitration catalyst based on the hierarchical porous SSZ-39 support obtained in this embodiment was used for NH3-SCR. The catalyst was tableted and sieved to 20-40 mesh. The SCR activity test was conducted using the following gas components: 500 ppm NH3, 500 ppm NO, and a balance of 5 vol% O2 and N2. The SCR activity of the catalyst was tested at a temperature range of 80-500°C, 1 standard atmosphere, and a gas hourly space velocity of 60,000 h⁻¹. -1 It is carried out under the following conditions.
[0059] Example 3
[0060] A method for preparing a copper-based denitration catalyst based on a hierarchical porous SSZ-39 support includes the following steps:
[0061] Step 1: 3.8g ZSM-5 zeolite was dispersed in 45.5g deionized water. Then, under continuous stirring, 35.45g sodium silicate, 28.45g N-methyl-N-ethyl-2,6-dimethylpiperidine hydroxide, 1.52g silica sol, 0.48g ammonium carbonate, and 0.38g copper acetate were added sequentially to the above solution, and the mixture was aged at 40℃ for 5h to obtain gel A. The obtained gel A was crystallized by stirring at 140℃ for 1h using a 450W microwave hydrothermal synthesis method. After cooling to room temperature, the obtained product was washed with deionized water and centrifuged for recovery. Subsequently, it was dried at 60℃ for 12h. After drying, the solid product was calcined in air at 550℃ for 8h and cooled to obtain hierarchical porous Cu-SSZ-39 molecular sieve.
[0062] Step 2: Dissolve 5.96g of copper acetate in 80g of deionized water to form a homogeneous solution. Add 2.69g of triethylenetetramine under continuous vigorous stirring to form a stable metal complex B. Then add 2g of the above-mentioned hierarchical porous molecular sieve and stir at 30℃ for 6h. After stirring, centrifuge to obtain a solid product. Then dry at 60℃ for 12h. After drying, calcine the solid product in air at 550℃ for 8h and cool to obtain a copper-based denitration catalyst based on the hierarchical porous SSZ-39 support.
[0063] In this embodiment, preferably, the continuous stirring and stirring speed are both 550 rpm, and the vigorous stirring speed is 1000 rpm.
[0064] The copper-based denitration catalyst based on the hierarchical porous SSZ-39 support obtained in this embodiment uses hierarchical porous SSZ-39 as the support and uniformly loads Cu and inducible CuO species as active sites.
[0065] The copper-based denitration catalyst based on the hierarchical porous SSZ-39 support obtained in this embodiment was used for NH3-SCR. The catalyst was tableted and sieved to 20-40 mesh. The SCR activity test was conducted using the following gas components: 500 ppm NH3, 500 ppm NO, and a balance of 5 vol% O2 and N2. The SCR activity of the catalyst was tested at a temperature range of 80-500°C, 1 standard atmosphere, and a gas hourly space velocity of 60,000 h⁻¹. -1 It is carried out under the following conditions.
[0066] Example 4
[0067] The only difference between this embodiment and Embodiment 1 is that:
[0068] In step 1, the aging process of gel A is as follows: the aging temperature is 20℃ and the aging time is 2h. After aging, gel A is synthesized by microwave hydrothermal synthesis (specifically, the microwave hydrothermal synthesis power is 300W, the heating temperature is 100℃, and the heating time is 4h). The obtained synthetic gel A is then heated and stirred at 100℃ for 0.5h to crystallize. After cooling to room temperature, the obtained product is washed with deionized water and centrifuged for recovery. Subsequently, it is dried at 40℃ for 4h. After drying, the solid product is calcined at 400℃ for 3h and cooled to obtain hierarchical porous Cu-SSZ-39 molecular sieve.
[0069] In step 2, after adding hierarchical porous Cu-SSZ-39 molecular sieve, the mixture is stirred at 10°C for 4 hours. After stirring, the solid product is obtained by washing and centrifugation. Then, it is dried at 40°C for 4 hours. After drying, the solid product is calcined at 400°C for 3 hours and cooled to obtain a copper-based denitration catalyst based on hierarchical porous SSZ-39 support.
[0070] Example 5
[0071] The only difference between this embodiment and Embodiment 1 is that:
[0072] In step 1, the aging process of gel A is as follows: the aging temperature is 100℃ and the aging time is 8h. After aging, gel A is synthesized by microwave hydrothermal synthesis (specifically, the microwave hydrothermal synthesis power is 600W, the heating temperature is 200℃, and the heating time is 48h) to obtain synthetic gel A. The obtained synthetic gel A is heated and stirred at 200℃ for 12h to crystallize. After cooling to room temperature, the obtained product is washed with deionized water and centrifuged for recovery. Then it is dried at 120℃ for 16h. After drying, the solid product is calcined at 650℃ for 12h and cooled to obtain hierarchical porous Cu-SSZ-39 molecular sieve.
[0073] In step 2, after adding hierarchical porous Cu-SSZ-39 molecular sieve, the mixture was stirred at 100℃ for 12h. After stirring, the solid product was obtained by washing and centrifugation. Then, it was dried at 120℃ for 16h. After drying, the solid product was calcined at 650℃ for 12h and cooled to obtain a copper-based denitration catalyst based on hierarchical porous SSZ-39 support.
[0074] Example 6
[0075] The only difference between this embodiment and Embodiment 1 is that:
[0076] In step 1, sodium carbonate is replaced with ferric carbonate, Y zeolite is replaced with MOR zeolite, sodium silicate and silica sol are replaced with amorphous silica, and 0.11g of copper nitrate is replaced with 0.22g of copper nitrate.
[0077] In step 2, triethylenetetramine is used to replace ammonia, and 60g of deionized water is used to replace 80g of deionized water.
[0078] Example 7
[0079] The only difference between this embodiment and Embodiment 1 is that:
[0080] In step 1, magnesium carbonate is used to replace sodium carbonate, nano-silica is used to replace sodium silicate, tetraethyl orthosilicate is used to replace silica sol, and 0.66g of copper nitrate is used to replace 0.22g of copper nitrate.
[0081] In step 2, ammonia is replaced with tetraethylenepentamine, and 80g of deionized water is replaced with 100g of deionized water.
[0082] Example 8
[0083] The only difference between this embodiment and Embodiment 1 is that:
[0084] In step 1, sodium silicate and silica sol are replaced with silica.
[0085] Comparative Example 1 (This comparative example does not contain any added salts compared to Example 1)
[0086] This comparative example provides an inductive CuO@Cu-SSZ-39 catalyst, the preparation method of which includes:
[0087] 1. 2.2 g of Y zeolite was dispersed in 20.83 g of deionized water. Then, under continuous stirring, 21.52 g of sodium silicate, 15.89 g of N,N-dimethyl-3,5-dimethylpiperidine hydroxide, 3.1 g of silica sol, and 0.22 g of copper nitrate were added sequentially to the above solution. The solution was aged at 40 °C for 5 h to obtain gel A. The obtained gel A was crystallized by microwave hydrothermal synthesis at 140 °C for 6 h. After cooling to room temperature, the obtained product was washed with deionized water and centrifuged for recovery. Then, it was dried at 60 °C for 6 h. After drying, the solid product was calcined in air at 550 °C for 8 h and cooled to obtain Cu-SSZ-39 molecular sieve.
[0088] 2. Dissolve 5.6g of copper nitrate in 80g of deionized water to form a homogeneous solution. Add 1.04g of ammonia water under continuous vigorous stirring to form a stable metal complex B. Then add 2g of the above molecular sieve and stir at 30℃ for 6h. After stirring, centrifuge to obtain a solid product. Then dry at 60℃ for 12h. After drying, calcine the solid product in air at 550℃ for 8h and cool to obtain an inductive CuO@Cu-SSZ-39 catalyst.
[0089] The inductive CuO@Cu-SSZ-39 catalyst obtained in this comparative example uses SSZ-39 as a support and Cu and inductive CuO species as active sites.
[0090] The induced CuO@Cu-SSZ-39 catalyst obtained in this embodiment was used for NH3-SCR. The catalyst was tableted and sieved to 20-40 mesh. The SCR activity was tested using the following gas composition: 500 ppm NH3, 500 ppm NO, and a balance of 5 vol% O2 and N2. The SCR activity of the catalyst was tested at a temperature range of 80-500°C, 1 standard atmosphere, and a gas hourly space velocity (VHSV) of 60,000 h⁻¹. -1 It is carried out under the following conditions.
[0091] Comparative Example 2 (This comparative example does not contain an inducing agent compared to Example 1)
[0092] This comparative example provides a CuO@hierarchical porous Cu-SSZ-39 catalyst, the preparation method of which includes:
[0093] 1. 2.2 g of Y zeolite was dispersed in 20.83 g of deionized water. Then, under continuous stirring, 21.52 g of sodium silicate, 15.89 g of N,N-dimethyl-3,5-dimethylpiperidine hydroxide, 3.1 g of silica sol, 0.48 g of sodium carbonate, and 0.22 g of copper nitrate were added sequentially to the above solution. The solution was aged at 40 °C for 5 h to obtain gel A. The obtained gel A was crystallized by microwave hydrothermal synthesis at 140 °C for 1 h. After cooling to room temperature, the obtained product was washed with deionized water and centrifuged for recovery. Then, it was dried at 60 °C for 12 h. After drying, the solid product was calcined in air at 550 °C for 8 h and cooled to obtain hierarchical porous Cu-SSZ-39 molecular sieve.
[0094] 2. Dissolve 5.6g of copper nitrate in 80g of deionized water to form a homogeneous solution, then add 2g of the above-mentioned hierarchical porous molecular sieve and stir at 30℃ for 6h; after stirring, centrifuge to obtain a solid product; then dry at 60℃ for 12h; after drying, calcine the solid product in air at 550℃ for 8h, and cool to obtain CuO@hierarchical porous Cu-SSZ-39 catalyst.
[0095] The CuO@hierarchical porous Cu-SSZ-39 catalyst obtained in this comparative example uses hierarchical porous SSZ-39 as a support and Cu and CuO species as active sites.
[0096] The CuO@hierarchical porous Cu-SSZ-39 catalyst obtained in this embodiment was used for NH3-SCR. The catalyst was pressed into tablets and sieved to 20-40 mesh. The contents of each component in the gas used for SCR activity testing were as follows: 500 ppm NH3, 500 ppm NO, and 5 vol% O2 and N2 balance gas. The SCR activity test of the catalyst was conducted at a temperature range of 80-500℃, 1 standard atmosphere, and a gas hourly space velocity of 60,000 h⁻¹.
[0097] Comparative Example 3 (This comparative example does not contain any salts or inducing agents compared to Example 1)
[0098] This comparative example provides a CuO@Cu-SSZ-39 catalyst, the preparation method of which includes:
[0099] 1. 2.2 g of Y zeolite was dispersed in 20.83 g of deionized water. Then, under continuous stirring, 21.52 g of sodium silicate, 15.89 g of N,N-dimethyl-3,5-dimethylpiperidine hydroxide, 3.1 g of silica sol, and 0.22 g of copper nitrate were added sequentially to the above solution. The solution was aged at 40 °C for 5 h to obtain gel A. The obtained gel A was crystallized by microwave hydrothermal synthesis at 140 °C for 6 h. After cooling to room temperature, the obtained product was washed with deionized water and centrifuged for recovery. Then, it was dried at 60 °C for 12 h. After drying, the solid product was calcined in air at 550 °C for 8 h and cooled to obtain Cu-SSZ-39 molecular sieve.
[0100] 2. Dissolve 5.6g of copper nitrate in 80g of deionized water to form a homogeneous solution, then add 2g of the above molecular sieve and stir at 30℃ for 6h; after stirring, centrifuge to obtain a solid product; then dry at 60℃ for 12h; after drying, calcine the solid product in air at 550℃ for 8h, and cool to obtain CuO@Cu-SSZ-39 catalyst.
[0101] The CuO@Cu-SSZ-39 catalyst obtained in this comparative example uses SSZ-39 as a support and Cu and CuO species as active sites.
[0102] The CuO@Cu-SSZ-39 catalyst obtained in this embodiment was used for NH3-SCR. The catalyst was tableted and sieved to 20-40 mesh. The SCR activity was tested using the following gas composition: 500 ppm NH3, 500 ppm NO, and a balance of 5 vol% O2 and N2. The SCR activity of the catalyst was tested at a temperature range of 80-500°C, 1 standard atmosphere, and a gas hourly space velocity of 60,000 h⁻¹. -1 It is carried out under the following conditions.
[0103] Comparative Example 4 (Cu-SSZ-39)
[0104] This comparative example provides a Cu-SSZ-39 catalyst, the preparation method of which includes:
[0105] 2.2 g of Y zeolite was dispersed in 20.83 g of deionized water. Then, 21.52 g of sodium silicate, 15.89 g of N,N-dimethyl-3,5-dimethylpiperidine hydroxide, and 3.1 g of silica sol were added to the solution sequentially under continuous stirring. The mixture was aged at 40 °C for 5 h to obtain gel A. Gel A was crystallized by microwave hydrothermal synthesis at 140 °C for 6 h. After cooling to room temperature, the product was washed with deionized water and centrifuged. It was then dried at 60 °C for 12 h. After drying, the solid product was calcined at 550 °C for 8 h and cooled to obtain Cu-SSZ-39 molecular sieve.
[0106] The Cu-SSZ-39 catalyst obtained in this embodiment was used for NH3-SCR. The catalyst was tableted and sieved to 20-40 mesh. The SCR activity was tested using the following gas composition: 500 ppm NH3, 500 ppm NO, and a balance of 5 vol% O2 and N2. The SCR activity of the catalyst was tested at a temperature range of 80-500°C, 1 standard atmosphere, and a gas hourly space velocity of 60,000 h⁻¹. -1 It is carried out under the following conditions.
[0107] Comparative Example 5 (This comparative example differs from Example 1 in that it contains water in the test conditions)
[0108] This embodiment provides a copper-based denitration catalyst based on a hierarchical porous SSZ-39 support, the preparation method of which includes:
[0109] 1. 2.2 g of Y zeolite was dispersed in 20.83 g of deionized water. Then, under continuous stirring, 21.52 g of sodium silicate, 15.89 g of N,N-dimethyl-3,5-dimethylpiperidine hydroxide, 3.1 g of silica sol, 0.48 g of sodium carbonate, and 0.22 g of copper nitrate were added sequentially to the above solution. The mixture was aged at 40 °C for 5 h to obtain gel A. The obtained gel A was crystallized by stirring at 140 °C for 1 h using a 450 W microwave hydrothermal synthesis method. After cooling to room temperature, the obtained product was washed with deionized water and centrifuged for recovery. Subsequently, it was dried at 60 °C for 12 h. After drying, the solid product was calcined at 550 °C for 8 h and cooled to obtain hierarchical porous Cu-SSZ-39 molecular sieve.
[0110] 2. Dissolve 5.6g of copper nitrate in 80g of deionized water to form a homogeneous solution. Add 1.04g of ammonia water under continuous vigorous stirring to form a stable metal complex B. Then add 2g of the above-mentioned hierarchical porous molecular sieve and stir at 30℃ for 6h. After stirring, centrifuge to obtain a solid product. Then dry at 60℃ for 12h. After drying, calcine the solid product in air at 550℃ for 8h and cool to obtain a copper-based denitration catalyst based on the hierarchical porous SSZ-39 support.
[0111] The copper-based denitration catalyst based on the hierarchical porous SSZ-39 support obtained in this embodiment uses hierarchical porous SSZ-39 as the support and uniformly loads Cu and inducible CuO species as active sites.
[0112] The copper-based denitration catalyst based on the hierarchical porous SSZ-39 support obtained in this embodiment was used for NH3-SCR. The catalyst was tableted and sieved to 20-40 mesh. The contents of each component in the gas used for SCR activity testing were as follows: 500 ppm NH3, 500 ppm NO, 5 vol% H2O, and 5 vol% O2 and N2 balance gas. The SCR activity of the catalyst was tested at a temperature range of 80-500°C, 1 standard atmosphere, and a gas hourly space velocity of 60,000 h⁻¹. -1 It is carried out under the following conditions.
[0113] Comparative Example 6 (The difference between this comparative example and Comparative Example 4 is that the test conditions include the presence of water)
[0114] This comparative example provides a Cu-SSZ-39 catalyst, the preparation method of which includes:
[0115] 2.2 g of Y zeolite was dispersed in 20.83 g of deionized water. Then, 21.52 g of sodium silicate, 15.89 g of N,N-dimethyl-3,5-dimethylpiperidine hydroxide, and 3.1 g of silica sol were added to the solution sequentially under continuous stirring. The mixture was aged at 40 °C for 5 h to obtain gel A. Gel A was crystallized by microwave hydrothermal synthesis at 140 °C for 6 h. After cooling to room temperature, the product was washed with deionized water and centrifuged. It was then dried at 60 °C for 12 h. After drying, the solid product was calcined at 550 °C for 8 h and cooled to obtain Cu-SSZ-39 molecular sieve.
[0116] The Cu-SSZ-39 catalyst obtained in this embodiment was used for NH3-SCR. The catalyst was pressed into tablets and sieved to 20-40 mesh. The SCR activity was tested using the following gas composition: 500 ppm NH3, 500 ppm NO, 5 vol% H2O, and 5 vol% O2 and N2 balance gas. The SCR activity of the catalyst was tested at a temperature range of 80-500°C, 1 standard atmosphere, and a gas hourly space velocity (VHSV) of 60,000 h⁻¹. -1 It is carried out under the following conditions.
[0117] from Figure 4 The comparison of denitrification performance shows that, compared with the comparative example and Cu-SSZ-39 without the addition of salts and inducers in the raw materials, the copper-based denitrification catalyst based on the hierarchical porous SSZ-39 support prepared in the embodiments of the present invention has a higher NO conversion rate, better low-temperature activity, and a wider temperature activity range, with a minimum ignition temperature T. 80Below 110℃, the NO conversion rate reaches over 90% within a temperature range of 120℃ to 500℃, and the NO conversion rate can reach 100% within a temperature range of 180℃ to 350℃. Under water content testing conditions, the catalyst of this invention can still maintain a NO conversion rate of over 90% within a temperature range of 120℃ to 500℃, demonstrating good water resistance.
[0118] The specific surface area of the catalyst in this invention is shown in Table 1 below.
[0119] Table 1 Specific surface area of catalysts
[0120]
[0121]
[0122] It should be understood that, in order to simplify this disclosure and aid in understanding one or more of the various aspects of the invention, features of the invention are sometimes grouped together in a single embodiment, figure, or description thereof in the above description of exemplary embodiments of the invention. However, this method of disclosure should not be interpreted as reflecting an intention that the claimed invention requires more features than expressly recited in each claim. Rather, as reflected in the claims, inventive aspects lie in fewer than all the features of the foregoingly disclosed embodiments. Therefore, the claims, following the detailed description, are hereby expressly incorporated into that detailed description, wherein each claim itself is a separate embodiment of the invention.
[0123] Although the invention has been described with reference to a limited number of embodiments, those skilled in the art will understand from the foregoing description that other embodiments are conceivable within the scope of the invention described herein. Furthermore, it should be noted that the language used in this specification has been chosen primarily for readability and instructional purposes, and not for the purpose of interpreting or limiting the subject matter of the invention. Therefore, many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the appended claims. The disclosure of the invention is illustrative and not restrictive, and the scope of the invention is defined by the appended claims.
[0124] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a copper-based denitration catalyst based on a hierarchical porous SSZ-39 support, characterized in that, Includes the following steps: Step 1: The silicon source, zeolite seed crystals, organic structure directing agent, deionized water, salt substances, and copper source are thoroughly mixed and then aged to obtain gel A. Gel A is synthesized by microwave hydrothermal synthesis. The obtained synthetic gel A is heated and stirred at 100~200℃ for 0.5~12h to crystallize. After cooling to room temperature, the obtained product is washed with deionized water and centrifuged for recovery. Then it is dried at 40~120℃ for 4~16h. After drying, the solid product is calcined at 400~650℃ for 3~12h and cooled to obtain hierarchical porous Cu-SSZ-39 molecular sieve. Step 2: Dissolve the copper source in deionized water to form a homogeneous solution, and add an inducing agent while stirring continuously to form a stable metal complex B; then add a hierarchical porous Cu-SSZ-39 molecular sieve and stir at 10~100℃ for 4~12h; after stirring, wash and centrifuge to obtain the solid product; Subsequently, the product was dried at 40~120°C for 4~16h; after drying, the solid product was calcined at 400~650°C for 3~12h, and after cooling, a copper-based denitration catalyst based on a hierarchical porous SSZ-39 support was obtained. The salts are selected from one of sodium carbonate, potassium carbonate, iron carbonate, magnesium carbonate, and ammonium carbonate. The inducing agent is selected from one of ammonia, ethylenediamine, triethylenetetramine, and tetraethylenepentamine.
2. The preparation method according to claim 1, characterized in that, In step 1, the mass ratio of zeolite seed crystals, silicon source, organic structure directing agent, deionized water, salt substances and copper source is 1: (8.69~11.19): (7.22~7.49): (9.47~11.97): (0.13~0.22): (0.05~0.30).
3. The preparation method according to claim 1, characterized in that, In step 2, the mass ratio of multi-level porous Cu-SSZ-39 molecular sieve, copper source, deionized water and inducer is 1: (2.8~3.725): (30~50): (0.52~1.345).
4. The preparation method according to claim 1, characterized in that, In step 1, The silicon source is selected from one or two of amorphous silica, nano silica, tetraethyl orthosilicate, silica sol, or sodium silicate; The zeolite seed crystals are selected from one of Y zeolite, Beta zeolite, ZSM-5 zeolite, or MOR zeolite; The organic structure directing agent is selected from one of N,N-diethyl-2,6-dimethylpiperidine hydroxide, N,N-dimethyl-3,5-dimethylpiperidine hydroxide, and N-methyl-N-ethyl-2,6-dimethylpiperidine hydroxide; The copper source is selected from one of copper nitrate, copper sulfate, and copper acetate.
5. The preparation method according to claim 1, characterized in that, In step 2, The copper source is selected from one of copper nitrate, copper sulfate, and copper acetate.
6. The preparation method according to claim 1, characterized in that, In step 1, the aging temperature of gel A is 20~100°C, and the aging time is 2~8h.
7. The preparation method according to claim 1, characterized in that, In step 1, the microwave hydrothermal synthesis power is 300~600W, the heating temperature is 100~200℃, and the heating time is 4~48h.
8. The copper-based denitration catalyst based on a hierarchical porous SSZ-39 support obtained by the preparation method according to any one of claims 1 to 7, characterized in that, Hierarchical SSZ-39 was used as a support, and Cu and induced CuO species were uniformly loaded as active sites.
9. The copper-based denitration catalyst based on the hierarchical porous SSZ-39 support according to claim 8, characterized in that, The specific surface area of the catalyst is 673~690 m². 2 / g.
10. The application of the copper-based denitration catalyst based on the hierarchical porous SSZ-39 support according to claim 8 in the selective catalytic reduction reaction NH3-SCR of ammonia.
Citation Information
Patent Citations
Molecular sieve based catalyst used for low-temperature SCR denitration and its preparation method
CN103599813A
Molecular sieve packaged core-shell catalyst and preparation method thereof
CN114749207A